Meta-adaptation in the auditory midbrain under cortical influence - Benjamin L. Robinson (Nature Portfolio, 2016)
Neurons in the auditory midbrain are known to modify their firing rates in response to changes in sound intensity. Here the authors show that in guinea pigs, such modifications occur faster when neurons re-encounter the same environment, a phenomenon they term meta-adaptation.